Handbook of research on critical examinations of neurodegenerative disorders - Sahab Uddin, Md., 1992-; Shah Amran, Md., 1969- (Medical Information Science Reference, 2019)
"This book provides a comprehensive overview of the neuronal degeneration that distributes the recent research to the scientific network. It also covers a wide range of topics for the neurophysiology and the neuropathology of the neurodegenerative diseases as well as current status and future opportunities and challenges"--Provided by publisher.